Reproductive biology of Myrtillocactus geometrizans (Cactaceae) flowers with contrasting orientation. Issue 3 (3rd April 2022) - Aguilar‐García, Sandra Aracely; Figueroa‐Castro, Dulce María; Valverde, Pedro Luis; Vite, Fernando; López‐Ortega, Gerardo; Pérez‐Hernández, Marco Aurelio
Abstract: In columnar cacti, a higher production of reproductive structures on branches oriented towards the Equator has been explained by their higher interception of photosynthetic active radiation (PAR) as well as resource availability. The goal of this study was to evaluate the effect of orientation on diverse aspects of the reproductive biology of Myrtillocactus geometrizans . Phenology was studied in north‐ and south‐facing branches. Floral cycle events, floral visitors, reproductive traits associated with sexual and attraction functions, and reproductive success were estimated from reproductive structures with contrasting orientation. Pollination experiments were conducted to evaluate the effect of orientation on mating system. Our results showed that south‐facing branches had a longer duration of the mature fruit phenophase. Moreover, flower synchrony, production of reproductive structures, and floral traits associated with the male (number of anthers and pollen grains per floral bud), female (number and size of ovules and dimensions of both ovary and ovary cavity), and attraction (petal size) functions had higher values in south‐facing flowers. The beginning and ending of the male function and the end of flower anthesis occurred earlier in south‐facing flowers. Diversity of floral visitors was similar between orientations, except for beetles whose abundance was greater in flowers oriented towards the south. North‐ and south‐facing flowers had a mixed mating system, with similar reproductive success. Our results showed strong differences in the reproductive biology of an intertropical columnar cactus, probably in response to the uneven PAR interception and resource availability in branches and flowers with contrasting orientation. Abstract :